Identifying the research process to analyse the adoption of the International Baccalaureate's Diploma Programme in England. (January 2018) - Outhwaite, Deborah
This article analyses the flow-line around the methodology used inside an educational research process that was originally established to examine the expansion of the International Baccalaureate's Diploma Programme (IBDP) in England. This article analyses the research question, then assesses the research focus, aims and objectives. The article then subsequently, briefly, critiques the research problem: how the expansion of the IBDP turned into a rapid decline of the qualification inside the post-16 state sector, so that the research process had to be amended. This article subsequently analyses the research problem that this generated: explaining the discussion of the flow-line, the reasons for the research method choice, and the chosen research paradigm and philosophy of critical realism. The research process analysed in this article comes from a completed Doctor of Education (EdD) which adhered to both the university's and BERA's (2011) ethical guidelines.